2019
DOI: 10.1590/1678-4499.2018044
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance and sweet corn quality as a function of inoculant doses (Azospirillum brasilense) and nitrogen fertilization management in summer harvest

Abstract: The inoculation of sweet corn seeds with Azospirillum brasilense in association to nitrogen fertilizer may be an agronomic alternative for increasing the crop yield and net income of plant growers. Therefore, the aim of this study was to investigate the effect of the different doses of inoculant (Azospirillum brasilense) associated to the nitrogen fertilization management on the phenotypic traits of one sweet corn hybrid in summer growing periods, under supplemental irrigation, in the Northwestern Paraná state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(40 reference statements)
0
2
0
3
Order By: Relevance
“…Inoculation of sweet corn seeds with Azospirillum brasilense in association with nitrogen fertilizer may be an agronomic alternative for increasing crop yield and net income of growers. Numoto et al [195] demonstrated that different rates of inoculation of sweet corn with Azospirillum brasilense integrated with nitrogen fertilization management improved phenotypic traits in summer growing periods, under supplemental irrigation. Furthermore, nitrogen fertilizer increased all the traits except kernel total sugars.…”
Section: Mycorrhizamentioning
confidence: 99%
“…Inoculation of sweet corn seeds with Azospirillum brasilense in association with nitrogen fertilizer may be an agronomic alternative for increasing crop yield and net income of growers. Numoto et al [195] demonstrated that different rates of inoculation of sweet corn with Azospirillum brasilense integrated with nitrogen fertilization management improved phenotypic traits in summer growing periods, under supplemental irrigation. Furthermore, nitrogen fertilizer increased all the traits except kernel total sugars.…”
Section: Mycorrhizamentioning
confidence: 99%
“…Regarding the number of applications of Azospirillum, we found that two applications are the best treatment for maize inoculation; for De Souza et al (2019), the application of 30 kg ha -1 of N at sowing and a single application of 150 kg ha -1 , or two applications of 75 kg ha -1 in topdressing, inoculated with Azospirillum brasilense provided better nutrition and development, with a positive effect for the mass of 100 grains which reflects an increase in grain yield, similarly as we found in the research. Also, the application dose of Azospirillum was important as found by Numoto et al (2019) who suggested that the dose of inoculant that provided the best agronomic result was 100 mL ha -1 in conjunction with the application of N at sowing or top dressing and as we found, in relation to Azospirillum application, that best performed when it considered two inoculations to maize foliage, for some characteristics such as ear weight, grain weight and ear length per plant.…”
Section: Discussionmentioning
confidence: 53%
“…Kadar gula biji jagung terus meningkat sampai waktu panen pukul 14.00 siang, hal disebabkan karena kebutuhan cahaya untuk proses fotosintesis cukup memenuhi persyaratan khususnya untuk tanaman dengan klasifikasi C4, dimana pada kondisi intensitas cahaya yang tinggi fotosintesis menjadi efektif. Dan pada intensitas cahaya yang tinggi biasanya berkorelasi positif dengan suhu, dan suhu akan mempengaruhi kerja enzim, untuk tanaman jagung manis suhu yang efektif untuk melakukan fotosintesis berkisar antara 30 -40 ˚C (Nahidah Bashir, 2012;Numoto et al, 2019;Subaedah et al, 2021).…”
Section: Panjang Diameter Dan Berat Tongkol Persampel Tingkat Kemanis...unclassified